PENGARUH FAKTOR-FAKTOR DALAM PERSPEKTIF FRAUD TRIANGLE TERHADAP FRAUDULENT FINANCIAL REPORTING (Studi Kasus pada Perusahaan Berdasarkan Sanksi dari Bapepam Periode 2008-2012) - Kurnia Kusuma Rachmawati; Marsono Marsono (Diponegoro Journal of Accounting, 2014)
The aim of this research was to analyze the factors of the fraud triangle in detecting fraudulent financial reporting. This research was replicated from the previous research, Hasnan et al. (2013). The difference between this research and the previous is in the object or the location. Previous study was done in Malaysia, while this research was done in Indonesia. In this research are added with independent variable, there are leverage, financial targets, and auditor switch. The addition of these variables into this research because of fraud triangle theory states that the above conditions favor the occurrence of fraudulent financial reporting. This researchis done to prove the influence of these variables on fraudulent financial reporting.The population of this research is the non financial companies listed in Indinesia Stock Exchange in 2008-2012. Total sample of this research is 50 non financial companies, consisting of 25 companies that make fraudulent financial reporting and 25 others are companies that do not commit fraud. Statistical data analysis method used is logistic regression.The result of this research shows that only factor multiple directorships (CROSSDIR) and auditor switch (CPA) has significant influence on fraudulent financial reporting. While other factors, foreign ownership (FOROWN), leverage (LEV), financial targets (ROA), effective monitoring (IND), related party transactions (RPT) has no significant influence on fraudulent financial reporting. The implications of this research note that the company is experiencing fraud reporting has high multiple directorships and a change of auditors in the period. It is important to know the factors that affect the fraudulent financial reporting to minimize fraud that occurred. So that the information used for decision making becomes relevant.